1996
DOI: 10.1111/j.1460-9568.1996.tb01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Dizocilpine Maleate (MK‐801) Treatment Suppresses the Effects of Nigrostriatal Dopamine Deafferentation on Enkephalin but not on Substance P Expression in the Rat Striatum

Abstract: The present study examined the effects of chronic treatment with dizocilpine maleate (0.2 mg/kg i.p., twice a day for 8 days) alone or in combination with unilateral 6-hydroxydopamine-induced lesion of the nigrostriatal dopaminergic neurons on substance P and enkephalin expression in the rat striatum. This was done by means of quantitative in situ hybridization histochemistry and immunocytochemistry. As reported previously, the unilateral dopaminergic lesion resulted in marked decreases in substance P mRNA exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

1997
1997
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 39 publications
5
17
0
Order By: Relevance
“…now et al 1990) or neutralization of the inhibitory effects of DA influence via D 2 receptors on striatopallidal neurons (Gerfen 1992;Hajji et al 1996). Our results showing increased Fos expression in the lateral striatum after administration of eticlopride, and decreased Fos expression in the medial striatum but not in the lateral striatum after administration of SCH-23390 plus eticlopride are in accordance with these previous reports of the effects of D 2 antagonists.…”
Section: Fos Induction By Treadmill Running In Non-pretreated Rats (Gsupporting
confidence: 83%
“…now et al 1990) or neutralization of the inhibitory effects of DA influence via D 2 receptors on striatopallidal neurons (Gerfen 1992;Hajji et al 1996). Our results showing increased Fos expression in the lateral striatum after administration of eticlopride, and decreased Fos expression in the medial striatum but not in the lateral striatum after administration of SCH-23390 plus eticlopride are in accordance with these previous reports of the effects of D 2 antagonists.…”
Section: Fos Induction By Treadmill Running In Non-pretreated Rats (Gsupporting
confidence: 83%
“…For instance, dopamine lesion is known to induce an increase in striatal glutamate transmission, and we recently provided evidence for an additional increase in L-DOPAtreated dyskinetic rats (Gubellini et al, 2006). Consistently, treatments with glutamate antagonists reduce both the increase in striatal PPE induced by dopamine lesion (Hajji et al, 1996) and the additional increase elicited by L-DOPA (Perier et al, 2002) as well as LID. However, striatal glutamate synaptic transmission is unlikely to mediate the cellular effects of STN-HFS reported here.…”
Section: Possible Neural Substrates Of the Striatal Interaction Betwesupporting
confidence: 49%
“…This is in agreement with previous data showing that striatal DA depletion (i.e., 6-OHDA lesion) resulted in increased expression of PPE mRNA (Cenci et al, 1993;Gerfen et al, 1991;Voorn et al, 1987). The increase in levels of PPE mRNA observed in 6-OHDA-lesioned striata after removing the inhibitory effect of DA on D 2 receptors is blocked by administra-tion of MK-801 or by corticostriatal deafferentation (Campbell and Björklund, 1994;Hajji et al, 1996). These results could be related to the observation that lack of stimulation of D 1 DA receptors decreases the conductance of NMDA-receptor-associated channels, while lack of stimulation of D 2 receptors increases the conductance of these channels (Cepeda et al, 1993).…”
Section: Rats Subjected To 5-ht And/or Da Denervationsupporting
confidence: 93%
“…Given that administration of FE in experimental conditions similar to those of the present study has been reported to induce release of DA in the striatum, and DA is usually considered to exert tonic inhibitory control over enkephalinergic neurons (see above), one would expect to find PPE mRNA levels decreased or unchanged after FE administration (Hurd and Herkehnham, 1992;Smith and McGinty, 1994). However, there is a great deal of evidence indicating that striatal neuropeptide gene expression is regulated not only by dopaminergic afferents but also by the glutamatergic corticostriatal system and the serotonergic system (Bath and Baraban, 1993;Campbell and Björklund, 1994;Hajji et al, 1996;Morris et al, 1988a). Similarly, it has been suggested that the striatal Fos expression induced by a dose of FE similar to that used in the present study is due to DA release, and specifically to dopaminergic stimulation of D 1 -receptor containing neurons (Hanson et al, 1991;Torres and Rivier, 1994;Torres, 1995); however, we have recently demonstrated that FE-induced Fos expression in striatal neurons involves interaction between the serotonergic, dopaminergic, and glutamatergic systems .…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation